Survival and Success of an Apocryphal Childhood of Jesus Reception of the Infancy Gospel of Thomas in the Middle Ages - Vukovic, Marijana (Berlin Boston De Gruyter, 2022)
This book explores the transformations of the Infancy Gospel of Thomas in the Middle Ages. It also connects the different representations of children, childhood, everyday- and family life in the distinct textual versions to the ancient and medieval settings in which they appear. The text survived and influenced ideas and mentalities that shaped medieval minds in the East and the West, but also enhanced anti-Jewish sentiments
Index
In English
Keywords: Christian literature, Early; Christian literature, Early -- History and criticism; Antijudaismus; Apokryphen des Neuen Testaments; Kindheit; Thomas der Apostel; Religion / Christianity / History; RELIGION / Biblical Criticism & Interpretation / General; Thomas the Apostle; New Testament Apocrypha; Childhood; Anti-judaism; RELIGION / Biblical Criticism & Interpretation / New Testament; Thomas the Apostle, New Testament Apocrypha, Childhood, Anti-Judaism; Hochschulschrift